Residual Biomass of Chenopodium Quinoa to Obtain an Eco-Friendly Product as a Biocide under the Concept of Circular Economy - Lucía Juez Arevalo; Elmer Benites-Alfaro; Felipa Muñoz Ccuro; Jorge Jave Nakayo; Carlos Cabrera Carranza; Danny Lizarzaburu Aguinaga; Jorge López Bulnes; Guido Rene Suca Apaza (Chemical Engineering Transactions)
The use of industrial insecticides is of growing concern in today's world due to their chemical composition and significant negative impacts on the environment and human health. These products contain toxic chemical compounds that can contaminate soil, water and air, affecting biodiversity and ecosystems in general. Faced with this problem, there is an urgent need to produce and use eco-friendly biocides as an alternative to industrial insecticides. Eco-friendly biocides are products that, instead of relying on harmful chemicals, are based on natural ingredients and environmentally friendly processes, are effective in controlling pests, and minimize risks to human health and the environment. The objective of the research was to take advantage of the residual biomass of Chenopodium quinoa in its scarification process, to extract the saponins and elaborate a natural biocide. The method consisted of a phytochemical screening for secondary metabolites to identify the saponins after a hydroalcoholic maceration process, at concentrations of 0, 25, 50 and 75 % ethanol To verify the biocidal property of the product, lethal dose tests were carried out on Premnotrypes vorax species, obtaining 100% with a solution of saponin and secondary metabolites in 75% ethanol at 240 min. Furthermore, the ratio of waste generated by the scarification process is 6 g per 1 kg, meaning that for every ton of Chenopodium quinoa processed, 600 kg of residual dust containing saponin would be obtained, which, if used under the concept of circular economy, would be obtained. 46.8 Liters per ton of natural bioinsecticide, environmentally friendly by avoiding chemical contamination and promoting sustainable agricultural practices.